2019
DOI: 10.1111/codi.14853
|View full text |Cite
|
Sign up to set email alerts
|

Extended thromboprophylaxis following colorectal surgery in patients with inflammatory bowel disease: a comprehensive systematic clinical review

Abstract: Aim Patients with inflammatory bowel disease (IBD) are at increased risk of postoperative venous thromboembolism (VTE) following major abdominal surgery. The pathogenesis is multifactorial and not fully understood. A combination of pathophysiology, patient and surgical risk factors increase the risk of postoperative VTE in these patients. Despite being at increased risk, IBD patients are not regularly prescribed extended pharmacological thromboprophylaxis following colorectal surgery. Currently, there is a pau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 74 publications
3
39
0
Order By: Relevance
“…IBD-related surgery has previously been reported to be one of the established risk factors of TED in multiple studies, with a higher risk observed in UC cases requiring colectomy than CD-related surgery. [25][26][27][28] The elevated risk of UC-related surgery probably reflects, in part, the higher inflammatory burden, and perhaps this is a population in which an increased understanding of genetic risk might have the largest impact. Importantly, genetic factors remained significant even after adjusting for age at last visit and history of IBD-related surgery (Supplementary Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…IBD-related surgery has previously been reported to be one of the established risk factors of TED in multiple studies, with a higher risk observed in UC cases requiring colectomy than CD-related surgery. [25][26][27][28] The elevated risk of UC-related surgery probably reflects, in part, the higher inflammatory burden, and perhaps this is a population in which an increased understanding of genetic risk might have the largest impact. Importantly, genetic factors remained significant even after adjusting for age at last visit and history of IBD-related surgery (Supplementary Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to consider the level of active inflammation present when determining whether to prescribe mechanical or chemical VTE prophylaxis to IBD patients undergoing colorectal surgery. Further, the duration of the postoperative proinflammatory, hypercoagulable state is not well-defined in children but has been shown to extend for up to two to six weeks in adults [14,15]. Our data found a median postoperative time of two weeks prior to DVT diagnosis, however there were a number of events that occurred much further out than that.…”
Section: Discussionmentioning
confidence: 54%
“…In fact, during the natural course of IBD, most CD patients undergo at least one surgical intervention (both intestinal resection or for perianal disease) and approximately 10% of UC patients undergo colectomy, usually with a subsequent construction of an ileo-anal pouch. However, surgery in IBD patients carries a significant VTE risk, despite adequate prophylaxis implementation [ 52 , 53 ]. In fact, a systematic review including 38 studies reported that the postoperative rates of VTE in IBD patients ranged from 0.6% to 8.9% [ 52 ].…”
Section: Surgerymentioning
confidence: 99%
“…However, surgery in IBD patients carries a significant VTE risk, despite adequate prophylaxis implementation [ 52 , 53 ]. In fact, a systematic review including 38 studies reported that the postoperative rates of VTE in IBD patients ranged from 0.6% to 8.9% [ 52 ]. The most important patient-specific risk factors for postoperative VTE are UC, increasing age and obesity, whereas surgery-specific risk factors include open surgery, emergent surgery and ileostomy creation [ 52 ].…”
Section: Surgerymentioning
confidence: 99%
See 1 more Smart Citation